10.1371/journal.pmed.0020297 (CrossRef Listing of Deleted DOIs, 2000)
Cervical cancer screening uptake in Kenya remains far below global targets, particularly in urban informal settlements where knowledge gaps persist despite widespread awareness campaigns. Understanding how knowledge shapes screening behavior is critical to explaining the persistent gap between willingness and action. The objective was to examine knowledge-related determinants of cervical cancer screening uptake among mothers aged 25-49 years in Kiandutu Informal Settlement, focusing on both main knowledge effects and interaction effects with awareness. A cross-sectional survey was conducted among 385 women. Screening behaviour was classified into three categories: Screened, Not Screened but Intends, and Not Screened, No Intention. Knowledge was measured using a composite index, and multinomial logistic regression, including interaction terms, was used to assess how knowledge and awareness jointly influence screening. Screening uptake was 48.8%. Only 18.2% of women with low knowledge had ever screened, and 62.1% had no intention to screen. Higher knowledge levels were strongly associated with screening (χ²(4) = 58.780, p < 0.001). Low knowledge independently predicted non-intention (AOR = 13.091, 95% CI: 5.526-31.013). The interaction model revealed a distinctive pattern: awareness without adequate knowledge sharply reduced intention to screen (Low Knowledge × Awareness AOR = 0.024, 95% CI: 0.003-0.219). Screening behaviour in informal settlements is shaped not by awareness alone but by the depth and accuracy of knowledge. Women require actionable understanding, not just exposure to health messages, to progress from awareness to screening intention and uptake. These findings highlight the importance of knowledge-dependent effects in cervical cancer screening behaviour.